Hydrogen storage properties of Zr2Co crystalline and amorphous alloys. (6th January 2021) - Han, Luhui; Huang, Huogen; Zhang, Pengguo; Ma, Ce; Wang, Xuefeng; Sang, Ge; Luo, Wenhua
Abstract: To further explore the application feasibility of Zr2 Co alloy in tritium-related fields, hydrogenation/dehydrogenation properties of this material of crystalline or amorphous structure, prepared by arc melting or melt spinning, were studied by pressure-composition temperature measurement, X-ray diffraction, differential scanning calorimeter, thermal desorption spectroscopy. It was found that the two kinds of Zr2 Co alloys can absorb hydrogen in a close full concentration of ~9 mmol/g, and may have similar equilibrium hydrogen pressure in the order of 10 −6  Pa at room temperature. In their hydrogenated samples various hydrides were observed to form, including ZrH2, Zr2 CoH5, ZrCoH3 and an amorphous one with gradually decreasing general thermostability. The amorphous alloy exhibited easier hydrogen induced disproportionation caused by highly stable ZrH2 and much slower hydrogen absorption kinetics. This disproportionation behavior of the crystalline alloy was found to be entirely suppressed by changing heating process. The results firmly indicate that crystalline Zr2 Co alloy could be more favorable for tritium treatment due to very low equilibrium pressure and the feasibility of eliminating the disproportionation. Highlights: Hydrogenation/dehydrogenation properties of amorphous Zr2 Co alloy were firstly studied. Hydrogen induced disproportionation due to ZrH2 formation was found for glassy Zr2 Co alloy. The disproportionation of crystalline Zr2 Co was eliminated by changing heating treatment.